Catalyst slurry, preparation method thereof, catalyst layer and membrane electrode

By using two-step ultrasonic processing technology in the catalyst slurry, nanofibers adsorb ionomers to form an orderly transmission network, the problem of random adsorption of ionomers in the catalytic layer is solved, and the protons, electrons and water of the membrane electrode are improved Transmission characteristics improve the performance of the membrane electrode.

CN119170815APending Publication Date: 2024-12-20STATE POWER INVESTMENT CORP HYDROGEN ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411240523.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing method of preparing catalytic layers leads to random adsorption of ionomers, affecting the uniformity of proton transport channels and the water gas mass transfer ability, and reducing the performance of membrane electrodes.

Method used

Using two-step low-frequency and low-power ultrasonic treatment methods, nanofibers are added to the catalyst slurry, so that ionomers are adsorbed on the surface of the nanofibers to form an orderly transmission network, improving the transmission characteristics of protons, electrons and water.

Benefits of technology

By introducing nanofibers, ionomers are evenly distributed, preventing accumulation, improving the performance of membrane electrodes, and reducing ohmic polarization. The process is simple and cost-effective, making it easier to promote industrially.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170815A_ABST
    Figure CN119170815A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fuel cells, and particularly relates to catalyst slurry, a preparation method thereof, a catalyst layer and a membrane electrode. The preparation method of the catalyst slurry provided by the invention comprises the following steps: (1) adding nanofibers into an organic solvent, carrying out first ultrasonic water bath treatment, then adding an ionomer solution, and carrying out second ultrasonic water bath treatment, so as to obtain a fibrous ionomer dispersion liquid; and (2) adding a catalyst aqueous solution into the fibrous ionomer dispersion liquid, and mixing to obtain catalyst slurry. According to the method, nanofibers are introduced into a catalyst layer, and ionomers are adsorbed on the surfaces of the nanofibers to form an ordered transmission network by adopting a two-step low-frequency and low-power ultrasonic treatment mode, so that the formed catalyst layer has efficient proton, electron and water transmission characteristics, and the performance of a membrane electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a catalyst slurry and a preparation method thereof, a catalyst layer and a membrane electrode. Background Art

[0002] Proton exchange membrane fuel cells have attracted close attention from various research institutions in recent years due to their high efficiency and environmental friendliness. As the core component of fuel cells, membrane electrode (MEA) usually consists of a gas diffusion layer, a catalyst layer and a proton exchange membrane.

[0003] The catalyst layer is an important component of the membrane electrode and an important place for the electrode reaction. The catalyst layer is a multi-scale porous composite structure composed of catalysts, carbon carriers, and perfluorosulfonic acid ion polymers (ionomers). The catalyst layer determines the battery performance by affecting the transmission characteristics of electrons, protons, reactants, and products.

[0004] Therefore, how to prepare a catalytic layer that can improve the performance of membrane electrode has received more and more attention. Summary of the invention

[0005] The present invention is based on the inventor's discovery and understanding of the following facts and problems:

[0006] At present, the preparation of the catalytic layer is usually done by mechanically mixing an ionomer solution or ionomer dispersion with a catalyst, and the ionomer is adsorbed on the catalyst surface to form a proton transport channel. However, the ionomer is randomly adsorbed on the catalyst surface, making the ionomer film covering the catalyst uneven in thickness; in addition, some ionomers accumulate at the active center, which seriously affects the mass transfer capacity of water and gas, resulting in a decrease in the redox reaction or a reduction in the three-phase reaction interface, thereby causing a decrease in the performance of the membrane electrode.

[0007] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the embodiments of the present invention provide a catalyst slurry and a preparation method thereof, wherein nanofibers are introduced into the catalyst layer, and a two-step low-frequency and low-power ultrasonic treatment method is used to adsorb ionomers on the surface of the nanofibers to form an ordered transmission network, so that the formed catalyst layer has high-efficiency proton, electron and water transmission characteristics, thereby improving the performance of the membrane electrode.

[0008] The method for preparing the catalyst slurry according to the embodiment of the present invention comprises the following steps:

[0009] (1) adding nanofibers to an organic solvent for a first ultrasonic water bath treatment, and then adding an ionomer solution for a second ultrasonic water bath treatment to obtain a fibrous ionomer dispersion;

[0010] (2) Adding the catalyst aqueous solution to the fibrous ionomer dispersion obtained in step (1), and mixing them to obtain a catalyst slurry.

[0011] The advantages and technical effects brought by the method for preparing the catalyst slurry of the embodiment of the present invention are as follows: 1. According to the method of the embodiment of the present invention, after two ultrasonic treatments, the aggregates of the ionomer are dissociated, so that more sulfonic acid groups exposed to the solvent are dissociated, thereby increasing the charge density on the ionomer chain, and the mutual adsorption of the ionomer main chain and the hydrophobic nanofibers enables the nanofibers themselves to have the function of proton conduction; 2. According to the method of the embodiment of the present invention, nanofibers are introduced into the catalytic layer through ultrasonic action, which can guide the uniform distribution of ionomers and prevent the accumulation of ionomers near the active sites; in addition, compared with the carbon carrier in the catalyst, the nanofibers with excellent conductivity are also conducive to the rapid transmission of electrons and reduce ohmic polarization; 3. According to the method of the embodiment of the present invention, after two ultrasonic treatments, the ionomers are spontaneously adsorbed on the surface of the nanofibers to form fibrous ionomers, and the ordered network structure constructed between the fibrous ionomers has high-efficiency proton, electron and water transmission characteristics, thereby improving the performance of the membrane electrode; 4. According to the method of the embodiment of the present invention, the process is simple, the production efficiency is high, no special equipment is required, the cost is low, and it is easy to promote and apply in industrial production.

[0012] In some embodiments, in step (1), the nanofibers include at least one of carbon nanofibers, conductive metal compound nanofibers, or conductive polymer nanofibers;

[0013] and / or, the length of the nanofiber is 1 to 50 μm, and the diameter of the nanofiber is 20 to 500 nm;

[0014] And / or, the organic solvent includes at least one of n-propanol, isopropanol or ethanol.

[0015] In some embodiments, in step (1), in the first ultrasonic water bath treatment and / or the second ultrasonic water bath treatment, the temperature of the water bath is 0-20°C, the time of the ultrasonic water bath treatment is 5-20 min, the frequency of the ultrasound is 20-50 Hz, and the ultrasonic power is 60-100 W.

[0016] In some embodiments, in step (1), the ionomer solution comprises a perfluorosulfonic acid resin solution;

[0017] And / or, the mass fraction of the ionomer in the ionomer solution is 20-30%;

[0018] And / or, the solvent for preparing the ionomer solution includes water.

[0019] In some embodiments, in step (1), the mass ratio of the nanofibers to the ionomer is (0.3-1):(2-5).

[0020] In some embodiments, in step (2), the catalyst is a cathode catalyst or an anode catalyst, the cathode catalyst includes at least one of a platinum-carbon catalyst or a platinum-cobalt alloy catalyst, and the anode catalyst includes a platinum-carbon catalyst;

[0021] and / or, the mass ratio of the catalyst to the ionomer is 1:(0.3-0.5);

[0022] And / or, the mixing process includes first performing a stirring process and then performing a ball milling process.

[0023] The embodiment of the present invention further provides a catalyst slurry, comprising a catalyst, nanofibers and ionomers, wherein the ionomers are adsorbed on the nanofibers to form fibrous ionomers;

[0024] Preferably, the nanofibers include at least one of carbon nanofibers, conductive metal compound nanofibers or conductive polymer nanofibers, the length of the nanofibers is 1 to 50 μm, and the diameter of the nanofibers is 20 to 500 nm;

[0025] Preferably, the mass ratio of the nanofiber to the ionomer is (0.3-1):(2-5);

[0026] Preferably, the mass ratio of the catalyst to the ionomer is 1:(0.3-0.5).

[0027] In some embodiments, the catalyst slurry is prepared by the above method.

[0028] The embodiment of the present invention further provides a catalyst layer, which is prepared by using the catalyst slurry prepared by the above preparation method or the above catalyst slurry.

[0029] An embodiment of the present invention further provides a membrane electrode, comprising the above-mentioned cathode / anode catalyst layer and a proton exchange membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a schematic diagram of the process for preparing a fibrous ionomer dispersion in step (1) of Example 1;

[0031] Figure 2 is the TEM image of carbon nanofiber;

[0032] Figure 3 It is a polarization curve diagram of the membrane electrode prepared in Example 1 and Comparative Examples 1, 2 and 3 under hydrogen / air conditions. DETAILED DESCRIPTION

[0033] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0034] The method for preparing the catalyst slurry according to the embodiment of the present invention comprises the following steps:

[0035] (1) adding nanofibers to an organic solvent for a first ultrasonic water bath treatment, and then adding an ionomer solution for a second ultrasonic water bath treatment to obtain a fibrous ionomer dispersion;

[0036] (2) Adding the catalyst aqueous solution to the fibrous ionomer dispersion obtained in step (1), and mixing them to obtain a catalyst slurry.

[0037] The preparation method of the catalyst slurry of the embodiment of the present invention is that after two ultrasonic treatments, the aggregates of the ionomer are disintegrated, so that more sulfonic acid groups exposed to the solvent are dissociated, thereby increasing the charge density on the ionomer chain, and the mutual adsorption of the ionomer main chain and the hydrophobic nanofibers makes the nanofibers themselves have the function of proton conduction; the nanofibers are introduced into the catalytic layer through the action of ultrasound, which can guide the uniform distribution of the ionomer and prevent the accumulation of the ionomer near the active site; in addition, compared with the carbon carrier in the catalyst, the nanofibers with excellent conductivity are also conducive to the rapid transmission of electrons and reduce ohmic polarization; after two ultrasonic treatments, the method spontaneously adsorbs the ionomer on the surface of the nanofiber to form a fibrous ionomer, and the ordered network structure constructed between the fibrous ionomers has high-efficiency proton, electron and water transmission characteristics, thereby improving the performance of the membrane electrode; the method has a simple process, high production efficiency, does not require special equipment, has low cost, and is easy to promote and apply in industrial production.

[0038] In some embodiments, preferably, in step (1), the nanofibers include at least one of carbon nanofibers, conductive metal compound nanofibers or conductive polymer nanofibers;

[0039] and / or, the length of the nanofiber is 1 to 50 μm, and the diameter of the nanofiber is 20 to 500 nm;

[0040] And / or, the organic solvent includes at least one of n-propanol, isopropanol or ethanol.

[0041] More preferably, the nanofiber is a carbon nanofiber. More preferably, the carbon nanofiber includes at least one of multi-walled carbon nanotubes (MWCNT), single-walled carbon nanotubes (SWCNT) or carbon nanofibers (VGCF);

[0042] And / or, the organic solvent comprises n-propanol.

[0043] In some embodiments, preferably, in the step (1), in the first ultrasonic water bath treatment and / or the second ultrasonic water bath treatment, the temperature of the water bath is 0-20°C, the time of the ultrasonic water bath treatment is 5-20 min, the frequency of the ultrasound is 20-50 Hz, and the ultrasonic power is 60-100 W.

[0044] In the embodiment of the present invention, two low-frequency and low-power ultrasonic treatments are used to promote the disintegration of ionomer aggregates without destroying the main chain structure.

[0045] In some embodiments, preferably, in step (1), the ionomer solution comprises a perfluorosulfonic acid resin solution;

[0046] And / or, the mass fraction of the ionomer in the ionomer solution is 20-30%;

[0047] And / or, the solvent for preparing the ionomer solution includes water.

[0048] Further preferably, the ionomer solution is added dropwise.

[0049] In the embodiments of the present invention, the ionomer solution used can be prepared by oneself, or a commercial ionomer aqueous solution can be directly purchased.

[0050] In some embodiments, preferably, in the step (1), the mass ratio of the nanofibers to the ionomer is (0.3-1):(2-5).

[0051] In the embodiment of the present invention, the dosage ratio of nanofibers and ionomers is preferably selected. An appropriate amount of nanofibers is conducive to forming a complete and effective transmission network, thereby improving the transmission efficiency of protons, electrons and water vapor in the catalytic layer. If the amount of nanofibers added is too small, it is not conducive to forming an effective transmission network. If too much nanofibers are added, it is not conducive to dispersion and the catalytic layer is thickened, thereby increasing the bulk mass transfer resistance.

[0052] In some embodiments, preferably, in step (2), the catalyst is a cathode catalyst or an anode catalyst, the cathode catalyst includes at least one of a platinum-carbon catalyst or a platinum-cobalt alloy catalyst, and the anode catalyst includes a platinum-carbon catalyst.

[0053] Further preferably, the platinum loading in the platinum-carbon catalyst is 40-60 wt %, and the platinum loading in the platinum-cobalt alloy catalyst is 40-60 wt %.

[0054] In the embodiment of the present invention, the catalyst is a cathode catalyst or an anode catalyst, and a cathode catalyst slurry and an anode catalyst slurry are formed accordingly, thereby forming a cathode catalyst layer or an anode catalyst layer in the process of preparing the membrane electrode.

[0055] In some embodiments, preferably, in step (2), the mass ratio of the catalyst to the ionomer is 1:(0.3-0.5);

[0056] And / or, the mixing process includes first performing a stirring process and then performing a ball milling process.

[0057] More preferably, the stirring treatment time is 0.5 to 2 hours, and the ball milling treatment time is 12 to 20 hours.

[0058] The embodiment of the present invention further provides a catalyst slurry, comprising a catalyst, nanofibers and ionomers, wherein the ionomers are adsorbed on the nanofibers to form fibrous ionomers;

[0059] Preferably, the nanofibers include at least one of carbon nanofibers, conductive metal compound nanofibers or conductive polymer nanofibers, the length of the nanofibers is 1 to 50 μm, and the diameter of the nanofibers is 20 to 500 nm;

[0060] Preferably, the mass ratio of the nanofiber to the ionomer is (0.3-1):(3-5);

[0061] Preferably, the mass ratio of the catalyst to the ionomer is 1:(0.3-0.5).

[0062] In some embodiments, preferably, the above-mentioned catalyst slurry is prepared by the above-mentioned method.

[0063] The embodiment of the present invention further provides a catalyst layer, which is prepared by using the catalyst slurry prepared by the above preparation method or the above catalyst slurry.

[0064] An embodiment of the present invention further provides a membrane electrode, comprising the above-mentioned cathode / anode catalyst layer and a proton exchange membrane.

[0065] The method for preparing the membrane electrode comprises the following steps:

[0066] (a) coating a cathode catalyst slurry and an anode catalyst slurry on a PTFE substrate, respectively, and drying the slurry to obtain a cathode catalyst layer and an anode catalyst layer;

[0067] (b) placing the cathode catalyst layer and the anode catalyst layer obtained in step (a) on both sides of the proton exchange membrane, and after hot pressing and transferring to remove the PTFE substrate, attaching the frame and the gas diffusion layer (GDL) on both sides to obtain a membrane electrode.

[0068] In some embodiments, preferably, the Pt loading in the cathode catalyst layer is 0.2 to 0.35 mg / cm 2 ;

[0069] And / or, the Pt loading in the anode catalyst layer is 0.05-0.06 mg / cm 2 .

[0070] In some embodiments, preferably, the thickness of the cathode catalyst layer is 4 to 9 μm;

[0071] And / or, the thickness of the anode catalyst layer is 1 to 5 μm.

[0072] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings.

[0073] Example 1

[0074] (1) Use Figure 1 The process shown is to prepare a fibrous ionomer dispersion: first, 0.1 g of nanocarbon fiber is dispersed in 20 ml of n-propanol, and then 3.4 g of commercial ionomer aqueous solution (the mass fraction of perfluorosulfonic acid resin ionomer is 25%) is added dropwise at a frequency of 40 Hz and a power of 80 W, and then the water bath ultrasound is continued for 20 min. During the ultrasound treatment, the water temperature is maintained at about 10 ° C to obtain a fibrous ionomer dispersion with an efficient transmission network. The fibrous ionomer dispersion is divided into two parts, one of which is used for pH testing and the other is used to prepare a catalyst slurry;

[0075] (2) preparing a catalyst slurry: adding 2 g of a platinum-cobalt alloy catalyst (platinum loading: 50 wt%) to 6 g of ultrapure water, stirring evenly with a magnetic stirrer, and adding the fibrous ionomer solution obtained in step (1), continuing magnetic stirring for 1 h, and then transferring the above mixed solution to a ball mill, and ball milling at room temperature for 20 h to obtain a cathode catalyst slurry; selecting a platinum-carbon catalyst (platinum loading: 50 wt%) to prepare an anode catalyst slurry, the preparation process is the same as the preparation process of the cathode catalyst slurry;

[0076] (3) Preparation of membrane electrode: The cathode catalyst slurry and the anode catalyst slurry prepared in step (2) were coated on the PTFE substrate respectively by laboratory doctor blade coating, and dried in a blast drying oven, wherein the platinum loading of the cathode catalyst layer was controlled to be 0.3±0.01 mg / cm 2 The anode catalyst layer loading is controlled to be 0.05±0.005mg / cm 2), the cathode catalyst layer and the anode catalyst layer are placed on both sides of the proton exchange membrane (G12), and after the PTFE substrate is torn off by hot pressing transfer, the frame and GDL are attached to both sides to obtain a membrane electrode (active area greater than 280cm 2 ), wherein the thickness of the cathode catalyst layer is about 7 μm, and the thickness of the anode catalyst layer is about 1.5 μm.

[0077] The length of the nanocarbon fiber used in the embodiment of the present invention is 5 to 20 μm and the diameter is 50 to 200 nm; the TEM image of the nanocarbon fiber is as follows Figure 2 shown.

[0078] Example 2

[0079] The preparation method of this embodiment is the same as that of Example 1, except that in step (1), the amount of nano-carbon fiber used is 0.12 g, and the amount of commercial ionomer aqueous solution used is 3.64 g.

[0080] Example 3

[0081] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (1), the time of the first water bath ultrasonic treatment is 20 min, and the time of the second water bath ultrasonic treatment is 10 min.

[0082] Example 4

[0083] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (1), the time of the first water bath ultrasonic treatment is 15 min, and the time of the second water bath ultrasonic treatment is 15 min.

[0084] Comparative Example 1

[0085] The preparation method is the same as that of Example 1, except that in step (1), the carbon nanofibers and the commercial ionomer aqueous solution are simultaneously added to the n-propanol solvent and ultrasonically treated for 30 min. Two ionomer dispersions are also prepared, one for pH testing and the other for preparing the catalyst slurry.

[0086] Comparative Example 2

[0087] The preparation method is the same as that of Example 1, except that in step (1), after adding the commercial ionomer aqueous solution, ultrasonic treatment is not performed, but stirring treatment is performed for 20 minutes before adding it to the aqueous solution of the catalyst. Similarly, two ionomer dispersions are prepared, one for pH testing and the other for preparing the catalyst layer slurry.

[0088] Comparative Example 3

[0089] The preparation method is the same as that of Example 1, except that in step (1), the commercial ionomer aqueous solution is first added to the n-propanol solvent and ultrasonicated for 20 minutes, then the nano-carbon fibers are added, mixed and stirred for 10 minutes, and then added to the catalyst aqueous solution. Similarly, two ionomer dispersions are prepared, one for pH testing and the other for preparing the catalyst layer slurry.

[0090] Comparative Example 4

[0091] (1) adding 2 g of platinum-cobalt alloy catalyst (platinum loading: 50 wt%) to 6 g of ultrapure water, and stirring the mixture magnetically to obtain a cathode catalyst aqueous solution;

[0092] (2) Preparation of catalyst slurry: first disperse 0.1 g of carbon nanofiber in 20 ml of n-propanol, and perform water bath ultrasonic treatment for 10 min at a frequency of 40 Hz and a power of 80 W; then add it to the cathode catalyst aqueous solution and perform water bath ultrasonic treatment for 10 min to obtain a mixed solution; finally, add 3.4 g of commercial ionomer aqueous solution (the mass fraction of perfluorosulfonic acid resin ionomer is 25%) dropwise to the mixed solution, and perform water bath ultrasonic treatment for 10 min to obtain a cathode catalyst slurry, and prepare two cathode catalyst slurries, one for pH testing and the other for preparing membrane electrodes; select a platinum carbon catalyst (platinum loading: 50 wt%) to prepare an anode catalyst slurry, and the preparation process is the same as that of the cathode catalyst slurry.

[0093] (3) Preparation of membrane electrode: The process of preparing the membrane electrode is the same as the process of step (3) in Example 1, and will not be repeated here.

[0094] Performance Test:

[0095] (1) IV performance: The membrane electrodes prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were placed in a test fixture and tested for IV performance under the same operating conditions (temperature: 80°C, pressure: 100 kPa / 100 kPa, and anode and cathode humidity less than 40%). The results of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown in Table 1. Figure 3 shown.

[0096] (2) The pH values ​​of the ionomer dispersions in Examples 1 to 4, Comparative Examples 1 to 3, and the cathode catalyst slurry prepared in Comparative Example 4 were tested as follows: At room temperature (25° C.), a pH meter was directly inserted into the ionomer dispersion or cathode catalyst slurry, and the pH value was directly read after it stabilized.

[0097] Table 1

[0098]

[0099] Table 2

[0100]

[0101] From Table 1, Table 2 and Figure 3 It can be seen from the data that in Examples 1 to 4, two-step water bath ultrasonic treatment is used to disintegrate the ionomer aggregates and adsorb them on the carbon fiber surface, so that more sulfonate groups exposed to the solvent are dissociated, thereby increasing the charge density on the ionomer chain, resulting in a lower pH value, and effectively reducing the ohmic impedance of the membrane electrode; the one-dimensional structured carbon fiber has a surface loaded with ionomers to form a continuous proton and electron transport network, improve the proton and electron conductivity, and enhance the performance of the membrane electrode. And the results of Examples 1 to 4 show that the total time of the two ultrasonic treatments is controlled unchanged, the time of the first water bath ultrasonic treatment and the second ultrasonic treatment are both controlled within 5 to 20 minutes, and the amount of nanofibers and ionomer aqueous solution is appropriately increased, which has little effect on the pH of the ionomer dispersion and the performance of the membrane electrode.

[0102] In Comparative Example 1, the nano-carbon fiber and the ionomer are mixed and then ultrasonically dispersed. Because the high concentration of ionomer segments are entangled with each other and adsorbed on the carbon fiber agglomerates, even ultrasonic treatment cannot completely disentangle the ionomer aggregates; after adding the catalyst, the ionomer agglomerates accumulate near the active sites, increasing the gas mass transfer resistance, flooding occurs under high current density, and the performance of the membrane electrode is sharply attenuated. In Comparative Examples 2 and 3, the ionomer and n-propanol solution or nano-carbon fiber and n-propanol solution are preferentially ultrasonically treated. Although the ionomer conformation can be changed to a certain extent, the depolymerization effect of the ionomer is worse than that of Example 1. The performance of the membrane electrode obtained is worse than that of the membrane electrode obtained in Comparative Example 1, but not as good as that of the membrane electrode obtained in Example 1. In Comparative Example 4, the total ultrasonic time is controlled to be unchanged, and three ultrasonic treatments are performed, each ultrasonic treatment time is 10 minutes, and the catalyst aqueous solution and nano-carbon fiber are mixed first and then the ionomer aqueous solution is added. The pH change of the cathode catalyst slurry in Comparative Example 4 is not obvious, indicating that this method does not affect the dispersion of the ionomer; however, since the ionomer and Pt in the catalyst have strong surface adsorption, the ionomer is preferentially adsorbed on the catalyst surface, leaving only a small amount of ionomer adsorbed on the surface of the nanocarbon fiber. The ionomer is preferentially adsorbed on the catalyst surface and cannot form an efficient transmission network, thereby affecting the performance of the membrane electrode.

[0103] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0104] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A method for preparing a catalyst slurry, It is characterized in that The following steps are involved: (1) adding nanofibers to an organic solvent for a first ultrasonic water bath treatment, and then adding an ionomer solution for a second ultrasonic water bath treatment to obtain a fibrous ionomer dispersion; (2) Adding the catalyst aqueous solution to the fibrous ionomer dispersion obtained in step (1), and mixing them to obtain a catalyst slurry.

2. The method for preparing the catalyst slurry according to claim 1, It is characterized in that In the step (1), the nanofibers include at least one of carbon nanofibers, conductive metal compound nanofibers or conductive polymer nanofibers; and / or, the length of the nanofiber is 1 to 50 μm, and the diameter of the nanofiber is 20 to 500 nm; And / or, the organic solvent includes at least one of n-propanol, isopropanol or ethanol.

3. The method for preparing the catalyst slurry according to claim 1, It is characterized in that In the step (1), in the first ultrasonic water bath treatment and / or the second ultrasonic water bath treatment, the water bath temperature is 0-20° C., the ultrasonic water bath treatment time is 5-20 min, the ultrasonic frequency is 20-50 Hz, and the ultrasonic power is 60-100 W.

4. The method for preparing the catalyst slurry according to claim 1, It is characterized in that In the step (1), the ionomer solution includes a perfluorosulfonic acid resin solution; And / or, the mass fraction of the ionomer in the ionomer solution is 20-30%; And / or, the solvent for preparing the ionomer solution includes water.

5. The method for preparing the catalyst slurry according to claim 1, It is characterized in that In the step (1), the mass ratio of the nanofibers to the ionomer is (0.3-1):(2-5).

6. The method for preparing the catalyst slurry according to claim 1, It is characterized in that In the step (2), the catalyst is a cathode catalyst or an anode catalyst, the cathode catalyst includes at least one of a platinum-carbon catalyst or a platinum-cobalt alloy catalyst, and the anode catalyst includes a platinum-carbon catalyst; and / or, the mass ratio of the catalyst to the ionomer is 1:(0.3-0.5); And / or, the mixing process includes first performing a stirring process and then performing a ball milling process.

7. A catalyst slurry, It is characterized in that The invention comprises a catalyst, nanofibers and an ionomer, wherein the ionomer is adsorbed on the nanofibers to form a fibrous ionomer; Preferably, the nanofibers include at least one of carbon nanofibers, conductive metal compound nanofibers or conductive polymer nanofibers, the length of the nanofibers is 1 to 50 μm, and the diameter of the nanofibers is 20 to 500 nm; Preferably, the mass ratio of the nanofiber to the ionomer is (0.3-1):(2-5); Preferably, the mass ratio of the catalyst to the ionomer is 1:(0.3-0.5).

8. The catalyst slurry according to claim 7, It is characterized in that The method is prepared according to any one of claims 1 to 6.

9. A catalytic layer, It is characterized in that The catalyst slurry is prepared by the preparation method according to any one of claims 1 to 6 or the catalyst slurry according to claim 7 or 8.

10. A membrane electrode, It is characterized in that It comprises the cathode / anode catalyst layer and the proton exchange membrane as claimed in claim 9.